Environmentally friendly high-speed train brake material and its preparation method and application

By optimizing the component ratio and process flow of copper-based powder metallurgy braking materials, the problem of the copper-based powder metallurgy braking materials producing a large amount of brake dust during the production and use process is solved, and a low dust emission and high-performance environmentally friendly high-speed train braking materials are achieved.

CN119753417APending Publication Date: 2025-04-04WUHAN RES INST OF MATERIALS PROTECTION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411795093.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Copper-based powder metallurgical braking friction materials generate a large amount of braking dust during production and use, which causes pollution to human health and the environment. It is difficult for the prior art to reduce dust emissions without affecting friction and wear performance.

Method used

Using braking materials based on copper, the components are optimized by optimizing the component ratio and process flow, including using iron as reinforcement components and graphite as lubricating components, combined with wet mixing technology and pressurized sintering technology, environmentally friendly high-speed train brake materials with low braking dust emissions are prepared.

Benefits of technology

On the basis of ensuring the consistency of friction and wear performance of brake materials, the emission of brake dust is significantly reduced, environmental pollution is reduced, production costs are reduced, and the material's wear resistance and service life are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753417A_ABST
    Figure CN119753417A_ABST
Patent Text Reader

Abstract

The invention discloses an environmentally friendly high-speed train brake material and a preparation method and application thereof, and belongs to the field of powder metallurgy technology. The raw materials of the environmentally friendly high-speed train brake material include a matrix component, a strengthening component, a lubricating component, and a friction component; in terms of mass percentage, the matrix component is 46%-54% copper, the strengthening component is 15%-18% iron, the lubricating component is 15%-20% graphite, and the friction component is 6%-8% ferrochrome and 8%-10% zirconium dioxide. The components of the present invention are simple, the raw materials are widely available, and the cost is low. While taking into account the service performance of the brake material, the emission of brake dust is reduced, which is conducive to reducing environmental pollution. In addition, the preparation method of the environmentally friendly high-speed train brake material is simple and easy to control, the production cost is low, and it has good applicability in industrial production. The present invention has good application prospects in practical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of powder metallurgy, and in particular to an environmentally friendly high-speed train braking material and a preparation method and application thereof. Background Art

[0002] The braking system is an indispensable component of high-speed trains, and its braking capacity is the fundamental guarantee for train operation safety and transportation capacity. The braking methods of high-speed trains mainly include electric braking and mechanical braking. During normal operation, when the braking speed is high, high-speed trains use a combination of electric braking and mechanical braking, with electric braking being preferred. When the braking force is insufficient, mechanical braking is used to supplement it, while at low speeds, the train relies solely on mechanical braking. In addition, when emergency braking occurs, high-speed trains need to implement electric braking and mechanical braking at the same time. It can be seen that mechanical braking is an indispensable braking method for high-speed trains. High-speed trains use brake pads to clamp brake discs to apply mechanical braking, which is greatly affected by the operating conditions and service environment of the train. The brake pads need to have good friction matching with the brake disc. Powder metallurgy brake materials have the characteristics of suitable and stable friction coefficient, good wear resistance, sufficient mechanical strength, good environmental adaptability, and good matching with matching materials. They are an ideal brake pad material.

[0003] Copper-based powder metallurgy brake friction materials are widely used in high-speed train brakes. They are multi-component, multi-phase composite materials consisting of a copper matrix, friction components and lubricating components. For example, the Chinese invention patent with publication number CN106399743A discloses an ultra-simple component powder metallurgy friction material for high-speed train brake pads. The friction material contains only six main components, and the mass percentage of each component is: copper 40%-55%, iron 8%-20%, zirconium dioxide 1%-10%, chromium iron 6%-15%, graphite 16%-22%, and molybdenum disulfide 1%-4%. The powder metallurgy friction material for high-speed train brake pads prepared by the invention has the advantages of ultra-simple material components, simple process and low cost, and its various performances meet the braking requirements of high-speed trains with a speed of 200-250 km / h and high-speed trains with a speed of 300-350 km / h and above. For another example, the Chinese invention patent with publication number CN116372163A provides a high-speed train brake pad material containing fibrous copper-based powder, the raw materials used include the following components by mass percentage: copper powder 35%-58%, iron powder 10%-20%, zirconium dioxide 2%-8%, ferrochrome powder 5%-15%, graphite 15%-20%, molybdenum disulfide 1%-5%; in the copper powder, the content of fibrous copper powder is greater than or equal to 45%; the particle size distribution of the fibrous copper powder is: copper powder with a particle size of less than 5 μm: 5 wt.%-6 wt.%; copper powder with a particle size of 5-20 μm: 59 wt.%-65 wt.%; and copper powder with a particle size greater than 20 μm and less than or equal to 45 μm: 30 wt.%-33 wt.%. It can be prepared by existing conventional powder metallurgy methods. The product obtained by this invention has high hardness, high shear strength and high compressive strength. Under high-energy braking conditions, its friction coefficient is more stable and the wear is lower.

[0004] However, copper-based powder metallurgy brake friction materials will produce a large amount of brake dust during the production process, which is harmful to human health. In order to protect the friction pair (generally cast iron friction disc) from damage during use, copper-based powder metallurgy brake friction materials sacrifice themselves and are worn, which inevitably produces wear debris (i.e. brake dust). The heavy metal elements (copper, chromium, etc.) present in brake dust will have a negative impact on human health and cause environmental pollution. Dust with smaller particle size will float in the air, causing air pollution, while dust with larger particle size will settle to the ground, causing pollution to water resources, soil, etc.

[0005] Air particulate matter is highly carcinogenic and harmful to the human body and has been listed as a Class I carcinogen. Among them, air particulate matter from traffic emissions has become another major pollution source after coal burning and industrial emissions. According to statistics, PM2.5 produced by vehicle braking is 1.3 times that of PM2.5. 10 Particulate matter accounts for about 20% of traffic emissions (including exhaust and non-exhaust) PM 108%-27% of the total particulate matter. With the vigorous promotion of new energy vehicles and the implementation of a series of measures such as the priority development of public transportation systems, environmental pollution caused by braking particulate matter emissions will gradually become the main source of transportation emissions.

[0006] In summary, under the premise of not affecting the friction and wear performance of brake materials, reducing the emission of brake dust during production and use and solving the adverse effects of dust on the environment have positive significance for improving the environmental friendliness of brake materials for high-speed trains. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, there is provided an environmentally friendly high-speed train brake material with low brake dust emission, simple components, wide raw material sources and low cost, wherein the raw materials include a matrix component, a reinforcing component, a lubricating component and a friction component; in terms of mass percentage, the matrix component is 46%-54% copper, the reinforcing component is 15%-18% iron, the lubricating component is 15%-20% graphite, and the friction component is 6%-8% ferrochrome and 8%-10% zirconium dioxide.

[0008] Preferably, the raw materials of the matrix component, the strengthening component, the lubricating component and the friction component are all in powder form.

[0009] Further preferably, in the matrix component, the copper powder particle size is less than 74 μm; in the strengthening component, the iron powder particle size is less than 74 μm; in the lubricating component, the graphite powder particle size is 150-600 μm; in the friction component, the ferrochrome powder particle size is 50-110 μm, and the zirconium dioxide powder particle size is 100-250 μm.

[0010] In a second aspect of the present invention, a method for preparing an environmentally friendly high-speed train brake material with convenient process and wide applicability is provided, comprising the following steps: S1. Weigh the base component, the strengthening component, the lubricating component, and the friction component according to the raw material ratio, and mix them to form a mixture; S2, pressing the mixed material into a target specification to obtain a compact; S3. The compact is subjected to pressure sintering to obtain an environmentally friendly high-speed train brake material.

[0011] Preferably, the specific steps of S1 are as follows: weighing the matrix component and the reinforcing component according to the raw material ratio, sieving and premixing to obtain a premix; then adding the lubricating component and the friction component to the premix to obtain a wet mix; finally, adding kerosene as a wet mixing medium to perform wet mixing to obtain a mixture.

[0012] Raw material powders tend to agglomerate and form large particles, which are difficult to disperse during the mixing process. Screening before premixing is conducive to making the finer raw material powders more evenly distributed, ensuring the consistency of the performance of the brake material after sintering. In actual operation, in order to control the particle size of copper and iron powders to an index below 74 μm, a 200-mesh standard sieve can be used to complete the screening process.

[0013] Further preferably, the kerosene is added in an amount of 0.8%-1.5% of the wet mix by mass percentage.

[0014] Further preferably, the wet mixing treatment time is 8-10 hours.

[0015] The wet mixing process is used to mix all the raw materials, which helps to mix the powders with large differences in particle size and density evenly, effectively prevent dust from appearing in the mixing, and prevent the movement process from having too much impact on the uniformity of the powder. Kerosene is used as the wet mixing medium, which meets the requirements of not chemically reacting with the raw materials, being volatile, and non-toxic. Kerosene diffuses on the surface of the powder particles and acts as a binder during the mixing process, strengthening the bonding between the powders and preventing powder segregation. It effectively avoids the problem of component segregation in the mixing process, makes the raw materials mixed evenly, further ensures the consistency of material properties and improves the friction and wear properties of the materials.

[0016] Preferably, in S2, the pressing pressure is 500-700 MPa, and the holding time is 3-5 s.

[0017] Preferably, in S3, the sintering temperature of the pressure sintering is 950-1000° C., the unit sintering pressure is 2-3 MPa, and the holding time is 2-4 h.

[0018] Preferably, in S3, the pressure sintering is performed under a protective atmosphere, and the protective atmosphere is hydrogen or decomposed ammonia.

[0019] In the process of the present invention, the pressing molding adopts a relatively large pressure, combined with the pressure sintering under a protective atmosphere, which is beneficial to further ensure the strength of the brake material, so that the brake material has the advantages of high strength, high and stable friction coefficient, good wear resistance, etc.

[0020] In the third aspect of the present invention, there is provided an application of the environmentally friendly high-speed train brake material of the first aspect of the present invention or the environmentally friendly high-speed train brake material prepared by the method of the second aspect, specifically as a brake material for preparing brake pads.

[0021] Based on the above technical solutions, the design concept and principle of the present invention are as follows: The environmentally friendly high-speed train brake material of the present invention uses copper as a matrix to ensure that it has good thermal conductivity and physical and mechanical properties. For traditional brake materials, the commonly used strengthening component in the copper matrix is ​​tin, while the present invention uses iron instead of expensive tin. Iron is added to the copper matrix as a key strengthening component, which reduces production costs and effectively improves the strength and heat resistance of the copper matrix. On the one hand, iron enhances the mechanical properties of the matrix, and on the other hand, it can also act as a friction component to adjust the friction coefficient and stabilize the braking process. During use, the wear debris is easily gathered near the hard phase under the obstruction of the hard phase on the friction surface, and melts to form a friction layer under the action of the thermal effect during the friction process, while iron helps to improve the strength of the friction layer, prevent more fine wear debris from detaching from the friction interface, and thus reduce the emission of brake dust. In this field, graphite and molybdenum disulfide are the two most widely used lubricating components. The present invention takes into account that the lubrication performance of molybdenum disulfide will deteriorate sharply in a humid atmosphere and under oxidizing conditions. Graphite has good chemical stability during the friction process and will not produce a large amount of dust due to chemical reactions, while molybdenum disulfide will oxidize rapidly within 420-430 ° C (molybdenum disulfide will oxidize to form molybdenum trioxide at high temperature, and molybdenum trioxide itself does not have lubricity, resulting in increased friction and dust). The generated oxidation products may change its crystal structure and tribological properties. The oxidation process is accompanied by the destruction of crystals, and these chemical changes will cause it to produce more dust during the friction process. In addition, in the atmospheric environment, water adsorption may cause the friction force and critical wear load of molybdenum disulfide to change, thereby affecting its stability during the friction process and promoting the generation of dust. Based on the above considerations, the present invention only uses graphite as a lubricating component, and by optimizing the raw material parameters of graphite, the load resistance, high temperature resistance and wear resistance of the brake material are sufficient to achieve the expected performance, the apparent hardness of the brake material is reduced, the wear resistance and braking stability of the material are improved, and the cost of the brake material is reduced.

[0022] The present invention uses ferrochrome and zirconium dioxide as friction components to play the role of increasing friction, wear resistance and anti-seizure, and improve the friction coefficient. Compared with the commonly used friction component silicon dioxide in the field, the hardness of the two friction components selected by the present invention is appropriate, the degree of damage to the friction pair during the braking process is relatively light, and the generation of brake dust from the brake friction pair is reduced.

[0023] In summary, the environmentally friendly high-speed train brake material provided by the present invention adopts reasonable components and their proportion design to achieve synergistic efficiency of each component. In addition, the material is prepared by adopting a reasonably designed preparation process. Under the premise of ensuring the service performance of the brake material, the emission of brake dust during the service of the brake material is reduced, thereby reducing the environmental pollution problems existing in the brake materials for high-speed trains in service.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides an environmentally friendly brake material for high-speed trains, which has simple components, a wide range of raw material sources, and the advantage of low cost. While taking into account the service performance of the brake material, it reduces the emission of brake dust, which is beneficial to reducing environmental pollution.

[0025] The invention provides a method for preparing an environmentally friendly high-speed train brake material, which has a simple and easy-to-control process, a low production cost and good applicability in industrial production.

[0026] The present invention provides an application of an environmentally friendly high-speed train brake material, which is used as a brake material for preparing brake pads and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a metallographic photograph of the environmentally friendly high-speed train brake material prepared in Example 1; Figure 2 The brake dust emission of the environmentally friendly high-speed train brake material prepared in Example 1; Figure 3 This is a metallographic photograph of the brake material for high-speed trains in service in Comparative Example 1; Figure 4 This is the brake dust emission of the brake material for high-speed trains in service in comparative example 1. DETAILED DESCRIPTION

[0028] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0029] In the following embodiments: The raw materials are all in powder form, and the specifications of each powder are as follows: copper powder <74 μm; iron powder <74 μm; graphite powder: 150-600 μm; ferrochrome powder: 50-110 μm; zirconium dioxide powder: 100-250 μm.

[0030] Example 1 The environmentally friendly high-speed train brake material of this embodiment is prepared by the following method: S1. According to the raw material ratio: 54% copper, 15% iron, 6% ferrochrome, 8% zirconium dioxide, and 17% graphite, weigh the corresponding raw materials; mix the copper powder and iron powder, and then sieve through a 200-mesh standard sieve to premix to obtain a premix; then pour the graphite powder, ferrochrome powder, and zirconium dioxide powder into the premix to obtain a wet mix; add 1.5% kerosene of the total weight of the wet mix, mix the powders, and put them into a three-dimensional mixer for wet mixing for 9 hours to obtain a mixture; S2, filling the mixture into a mold, and pressing it into a target specification by a powder hydraulic press, with a pressing pressure of 650 MPa and a holding time of 5 s to obtain a compact; S3. The compact is stacked on a copper-plated steel back plate and placed in a sintering furnace for pressure sintering under hydrogen protection. The sintering temperature is 950 °C, the unit sintering pressure is 3 MPa, and the insulation time is 4 h to obtain an environmentally friendly high-speed train brake material.

[0031] Example 2 The environmentally friendly high-speed train brake material of this embodiment is prepared by the following method: S1. According to the raw material ratio: 51% copper, 18% iron, 8% ferrochrome, 8% zirconium dioxide, and 15% graphite, weigh the corresponding raw materials; mix the copper powder and iron powder, and then sieve through a 200-mesh standard sieve to premix to obtain a premix; then pour the graphite powder, ferrochrome powder, and zirconium dioxide powder into the premix to obtain a wet mix; add 0.8% kerosene of the total weight of the wet mix, mix the powders, and put them into a three-dimensional mixer for wet mixing for 10 hours to obtain a mixture; S2, filling the mixed material into a mold, and pressing it into a target specification by a powder hydraulic press, with a pressing pressure of 550 MPa and a holding time of 4 s to obtain a green compact; S3. The compact is stacked on a copper-plated steel back plate and placed in a sintering furnace for pressure sintering under the protection of decomposed ammonia. The sintering temperature is 980 ° C, the unit sintering pressure is 2.5 MPa, and the holding time is 2.5 h to obtain an environmentally friendly high-speed train brake material.

[0032] Example 3 The environmentally friendly high-speed train brake material of this embodiment is prepared by the following method: S1. According to the raw material ratio: 46% copper, 18% iron, 8% ferrochrome, 10% zirconium dioxide, and 18% graphite, weigh the corresponding raw materials; mix the copper powder and iron powder, and then sieve through a 200-mesh standard sieve to premix to obtain a premix; then pour the graphite powder, ferrochrome powder, and zirconium dioxide powder into the premix to obtain a wet mix; add kerosene accounting for 1.0% of the total weight of the wet mix, mix the powders, and put them into a three-dimensional mixer for wet mixing for 8 hours to obtain a mixture; S2, filling the mixed material into a mold, and pressing it into a target specification by a powder hydraulic press, with a pressing pressure of 500 MPa and a holding time of 3 s to obtain a green compact; S3. The pressed blank is stacked on a copper-plated steel back plate and placed in a sintering furnace for pressure sintering under hydrogen protection. The sintering temperature is 950 °C, the unit sintering pressure is 2 MPa, and the holding time is 2 h to obtain an environmentally friendly high-speed train brake material.

[0033] Example 4 The environmentally friendly high-speed train brake material of this embodiment is prepared by the following method: S1. According to the raw material ratio: 48% copper, 18% iron, 6% ferrochrome, 8% zirconium dioxide, and 20% graphite, the corresponding raw materials are weighed; copper powder and iron powder are mixed well and premixed through a 200-mesh standard sieve to obtain a premix; then graphite powder, ferrochrome powder, and zirconium dioxide powder are poured into the premix to obtain a wet mix; 1.0% kerosene of the total weight of the wet mix is ​​added and the powder is mixed well, and the powder is loaded into a three-dimensional mixer for wet mixing for 8 hours to obtain a mixture; S2, filling the mixed material into a mold, and pressing it into a target specification by a powder hydraulic press, with a pressing pressure of 700 MPa and a holding time of 2 s to obtain a green compact; S3. The compact is stacked on a copper-plated steel back plate and placed in a sintering furnace for pressure sintering under hydrogen protection. The sintering temperature is 1000 °C, the unit sintering pressure is 2 MPa, and the holding time is 2 h to obtain an environmentally friendly high-speed train brake material.

[0034] Comparative Example 1 This comparative example uses brake materials for high-speed trains currently in service that are commercially available from Jiangxi Huawu Brake Co., Ltd.

[0035] Comparative Example 2 The preparation method of the high-speed train brake material of this comparative example is basically the same as that of Example 3, except that kerosene is not added to S1 of this comparative example for mixing.

[0036] Test Example 1 This test case studies the comprehensive performance of environmentally friendly high-speed train brake materials in practical applications.

[0037] The mechanical properties and friction and wear properties of the brake materials of the embodiment and the comparative example were tested respectively. The apparent hardness of the brake material was tested using a Brinell hardness tester. The shear strength of the brake material was tested using a universal material testing machine.

[0038] The brake disc material used in high-speed trains was used as the matching material (i.e. 30CrSiMoVA). A pin-on-disc friction and wear testing machine was used to simulate the braking conditions of a high-speed train at a running speed of 300 km / h. The friction and wear properties of the brake material, such as the friction coefficient, wear rate, and brake dust emissions of the brake material, were tested.

[0039] Instantaneous friction factor ( μ i ) is calculated by converting the collected tangential force ( f ) divided by the normal force (F): .

[0040] Average friction factor ( μ a ) is calculated as follows: ; Where t is the friction test time.

[0041] Wear rate ( ω i ) is calculated as follows: ; In the formula, m b is the mass of the brake material sample before the test, m a is the mass of the brake material sample after the test, and L is the total friction distance of the brake material sample.

[0042] The brake dust test method is as follows: place the sample in a closed space, control the constant air flow rate, place the particle counter sampling port near the friction surface, pre-collect the background particle concentration in the closed space, conduct a friction and wear test after 30 minutes, and collect the brake dust emission data during the friction process.

[0043] The metallographic images of the brake materials of Example 1 and Comparative Example 1 are observed in combination with the photos. The metallographic images of the environmentally friendly high-speed train brake material prepared in Example 1 are as follows: Figure 1 As shown in Figure 2, the brake dust emission is as follows: Figure 2 The metallographic photograph of the brake material for high-speed trains in service in Comparative Example 1 is shown in FIG. Figure 3 As shown in Figure 2, the brake dust emission is as follows: Figure 4 The test results of mechanical properties and friction and wear properties of brake materials are shown in Table 1.

[0044] Table 1: Mechanical properties and friction and wear properties of brake materials

[0045] It can be seen from Table 1 that compared with the brake material for high-speed trains currently in service in Example 1, the shear strength of the environmentally friendly brake material for high-speed trains provided by the present invention is greatly improved, and the incidence of damage such as edge collapse and cracking of the brake material is reduced. The reduction in the apparent hardness of the present invention can achieve smooth braking, improve the comfort of the braking process, and reduce the wear of the brake disc. It can be seen from the friction and wear test data that compared with the brake material for high-speed trains currently in service in Example 1, the friction coefficient of the environmentally friendly brake material for high-speed trains of the present invention is slightly improved, which can reduce the braking distance of the train to a certain extent; the wear rate of the brake material is reduced, and the wear resistance is effectively improved.

[0046] Depend on Figure 1 It can be seen that the components of the environmentally friendly high-speed train brake material are evenly distributed, tightly combined, and have no microcracks. Figure 3The components of the brake material for high-speed trains in service are evenly distributed. The metallographic structure of the brake material prepared by the present invention reaches the index of practical application. Figure 2 The results show that the peak emission of particulate matter (0.3 μm) per unit time of environmentally friendly high-speed train brake materials is 2.3×10 5 In contrast, Figure 4 This indicates that the peak emission of particulate matter (0.3 μm) per unit time of brake materials used in current high-speed trains is 3.2×10 5 .Depend on Figure 2 , 4 It can be seen that the brake dust emission generated by the brake material provided by the present invention is reduced by about 1 / 3, thereby reducing pollution to the environment and being environmentally friendly.

[0047] Based on the above test results, the brake material for high-speed trains provided by the present invention has less damage to the brake disc, increases the service life of the brake pad and brake disc, reduces the operation and maintenance cost of high-speed trains, and is environmentally friendly. It can be seen that the use of the brake material provided by the present invention makes the operation of high-speed trains safer, more reliable, more economical, and more environmentally friendly.

[0048] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. An environmentally friendly high-speed train brake material, characterized in that: The raw materials of environmentally friendly high-speed train brake materials include matrix components, strengthening components, lubricating components, and friction components; in terms of mass percentage, the matrix component is 46%-54% copper, the strengthening component is 15%-18% iron, the lubricating component is 15%-20% graphite, and the friction component is 6%-8% ferrochrome and 8%-10% zirconium dioxide.

2. The environmentally friendly high-speed train brake material according to claim 1, characterized in that: The raw materials of the matrix component, the strengthening component, the lubricating component and the friction component are all in powder form.

3. The environmentally friendly high-speed train brake material according to claim 2, characterized in that: In the matrix component, the powder particle size of copper is less than 74 μm; in the strengthening component, the powder particle size of iron is less than 74 μm; in the lubricating component, the powder particle size of graphite is 150-600 μm; in the friction component, the powder particle size of ferrochrome is 50-110 μm, and the powder particle size of zirconium dioxide is 100-250 μm.

4. A method for preparing an environmentally friendly high-speed train brake material as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1. Weigh the base component, the strengthening component, the lubricating component, and the friction component according to the raw material ratio, and mix them to form a mixture; S2, pressing the mixed material into a target specification to obtain a compact; S3. The compact is subjected to pressure sintering to obtain an environmentally friendly high-speed train brake material.

5. The method for preparing an environmentally friendly high-speed train brake material according to claim 4, characterized in that: The specific steps of S1 are as follows: weigh the base component and the reinforcing component according to the raw material ratio, sieve and premix them to obtain a premix; then add the lubricating component and the friction component to the premix to obtain a wet mix; finally, add kerosene as a wet mixing medium to perform wet mixing to obtain a mixture.

6. The method for preparing an environmentally friendly high-speed train brake material according to claim 5, characterized in that: In terms of mass percentage, the amount of kerosene added is 0.8%-1.5% of the wet mix; the wet mix treatment time is 8-10 hours.

7. The method for preparing an environmentally friendly high-speed train brake material according to claim 4, characterized in that: In S2, the pressing pressure is 500-700 MPa, and the holding time is 3-5 s.

8. The method for preparing an environmentally friendly high-speed train brake material according to claim 4, characterized in that: In the S3, the sintering temperature of the pressure sintering is 950-1000°C, the unit sintering pressure is 2-3 MPa, and the holding time is 2-4h.

9. The method for preparing an environmentally friendly high-speed train brake material according to claim 4, characterized in that: In S3, the pressure sintering is performed under a protective atmosphere, and the protective atmosphere is hydrogen or decomposed ammonia.

10. An application of the environmentally friendly high-speed train brake material according to any one of claims 1 to 3 or the environmentally friendly high-speed train brake material prepared by the preparation method according to any one of claims 4 to 9, characterized in that: Used as brake material to prepare brake pads.

Citation Information

Patent Citations

  • Super-simple component powder metallurgy friction material for high-speed train brake pad

    CN106399743A

  • High-speed train brake pad material containing fibrous copper-based powder

    CN116372163A